Implementation halal certification for creative economy business actors in the food and beverage sub-sector - Handoko Sosro Hadi Wijoyo; Moh. Saiful Anam; Bagus Isyanto (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
The term halal has been associated with Islam in various areas. The main focus of this service is halal certification and standards. The process involves verifying the authenticity of halal food and compliance with Islamic principles. Culture dominates creative economic businesses in Indonesia. Halal certification obtained by the APMMJ community can provide self-confidence in business, and the implementation of community service by involving the community will be very effective, they can also become intermediaries in other business actors to socialize the importance of halal certification and can become a companion for halal products to accelerate government programs on halal in the future. This service prioritizes facilitation by involving experienced cross-sectoral creative economy methods, the implementation of which includes assistance in making NIB, PIRT, Halal Certification, and more professional product photos, cross-sector creative assistance methods make the business community in APMMJ obtain a good business spirit both moral and material.